THE EFFECT OF REALISTIC MATHEMATHIC EDUCATION MODELS ON MATHEMATICAL REASONING ABILITY REVIEWED FROM STUDENT’S LEARNING STYLES - Apriani, Dini; Mujib, Mujib; Pratiwi, Dona Dinda (ZERO: Jurnal Sains, Matematika dan Terapan, 2019)
Abstract This study aims to see the effect of realistic mathemathic education modelson students' mathematical reasoning abilities in terms of learning styles. This type ofresearch is quantitative. Data collection techniques used were essay tests andinterviews. The data analysis technique used is hypothesis testing using 2-way anava.But before the anava test is carried out, the normality, homogeneity and balance testsare performed. Based on the data that is known that normal data, based on the sameand balanced variance obtained by the 2-way Anova test results indicate that thereis an influence of the RTE model on students' mathematical reasoning ability, namelythe reasoning ability of students with RME model treatment is better than themathematical reasoning ability with conventional treatment methods. In additionthere is the influence of student learning styles on students' reasoning abilities.Furthermore, mathematical reasoning ability of students who have who have a visuallearning style is better than students who have an auditory and kinesthetic learningstyle. While students who have kinesthetic learning styles are better than studentswho have auditory learning styles. There is no interaction between the treatment oflearning with the learning styles category of students. Means, there is no differencein the effect between the learning treatment and learning styles of students on theability of mathematical reasoning on students with the treatment of learning usingthe Realistic Mathematics Education model or using conventional learning models.Key Word: Realistic Mathematical Education Model, MathematicalReasoning Ability, Learning Styles